Kedudukan Hukum Legalisasi Notaris Terhadap Visi Dan Misi Calon Kepala Daerah - Muhammad Khaidir; Syamsul Bachri; Zulkifli Aspan (Indonesian Journal of Criminal Law, 2021)
The Research objective to analyze the function and legal power of notary legalization as an authorized official to make legalization of work programs that are part of the Vision and Mission of candidates for regent and deputy regent. This type of research is a normative legal research. The results of this study indicate that, firstly, the function of notary legalization of the political contract of regional head candidates, is to convince prospective voters and attract voters' sympathizers by being legalized at a notary, secondly, the legal force of notary legalization formally has legal legality but substantially remains the responsibility of the head candidate. the area that makes the vision and mission. Because notary legalization serves to provide signature certainty and certainty of the date of signing of agreements made under the hand which are only binding on the parties and, in general the strength of proof of legalization of private deed lies in the affixing of signatures by the parties, in this case judges or third parties cannot denying the truth of the signature on the deed under the hand that has been legalized before a notary, because the notary has explained at the end of the deed that the deed has been signed before him. Penelitian ini bertujuan menganalisis fungsi dan kekuatan hukum legalisasi notaris sebagai pejabat yang berwenang untuk membuat legalisasi terhadap program kerja yang menjadi bagian dari Visi dan Misi calon bupati dan wakil bupati. Tipe penelitian ini merupakan penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa, pertama, fungsi legalisasi Notaris terhadap kotrak politik calon kepala daerah,adalah untuk meyakinkan calon pemilih dan menarik simpatisan pemilih dengan dilegalisasi di notaris, kedua kekuatan hukum legalisasi notaris secara formal memiliki legalitas hukum tetapi secara substansi tetap menjadi tanggungjawab calon kepala daerah yang membuat visi misi tersebut. Karena legalisasi notaris berfungsi untuk memberi kepastian tandatangan dan kepastian tanggal penandatangan perjanjian yang dibuat dibawah tangan yang sifatnya hanya mengikat pihak dan, secara umum kekuatan pembuktian legalisasi akta di bawah tangan terletak pada pembubuhan tanda tangan oleh pihak, dalam hal ini hakim ataupun pihak ketiga tidak dapat menyangkal kebenaran tanda tangan pada akta di bawah tangan yang telah dilegalisasi dihadapan notaris, sebab notaris telah menerangkan dalam akhir aktanya bahwa akta tersebut telah ditandatangani dihadapannya.